Experience of Integrated Learning Among Theological Students in Jos Metropolis and Environs - Samuel Ango; Gonjing Chorwunna (African Theological Journal for Church and Society)
Teaching and learning in institutions established by Christians generally reflect the fragmented approach to education that has for long characterized Western education, such that faith and learning are splintered because of dualism which advocates separation of Church and State, subjects are taught as if they are independent of other subjects and often as if they are unrelated to life, thus missing out the connectivity that makes learning meaningful and useful. Consequently, both in Church and secular life Christians often seem unable to apply biblical knowledge to solving life’s problems. In the belief that integrated learning, which is gaining recognition globally, can improve the application of knowledge to life to increase productivity and meaningful living among Christians, these researchers investigated the extent to which theological students in Jos and its environs in Nigeria may be experiencing integrated learning, using a descriptive survey method. The research found that integrated learning takes place randomly but without cognitive recognition among the students, and recommends more intentional description and application of its principles in teaching and learning in theological institutions, so that there might be greater evidence of integration of learning in both spiritual and secular life among Christians.